Analisis Kinerja Keuangan Unit Usaha Pamdes Pada Bumdes Bina Sejahtera Kembang Kerang Kabupaten Lombok Timur - Nurlaili Ayu Lestari; Herlina Pusparini; Adhitya Bayu S (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
Local Water Company – Perusahaan Air Minum Desa (PAMDes hereafter) is a unit of local business that aims to manage and distribute clean water to local communities. This study aims at examining the financial performance of PAMDes Kembang Kerang based on four different ratios; liquidity, solvability, profitability, and activity. The method used in the current study was documentation in the form of the PAMDes financial reports from 2017 to 2020. To triangulate the data, semi-structured interviews were employed with the PAMDes staff. While the data gained from documentation were described quantitatively, the interview data were analyzed qualitatively. The current study results showed that from 2017 to 2020, the liquidity ratio for the first three consecutive years was infinity (very good), 9.09% (not good). For successive solvability ratios in three years were 0 (very good), 20.58% (very good). Meanwhile, the profitability ratios in a row from 2017 to 2020 NPM were 7.01% (good enough), -19.16% (not good), 8.88% (good enough), -24.8% (not good ). Meanwhile, ROA was 84,36 (very good), -12.8% (not good), 9.85% (good), -3.89% (not good). The last is the activity ratio obtained 12.03 times (very good), 0.67 times (not good), 1.11 times (not good), and 0.16 times (not good)